Production Management Model Based on Lean Manufacturing and Change Management Aimed at Reducing Order Fulfillment Times in Micro and Small Wooden Furniture Companies in Peru - Castro-Chara, R. (2020)
This research study seeks to identify and prioritize the causes of order fulfillment delays in a small wooden furniture manufacturing company. The authors propose a 5-phase Lean Optimization model to address and reduce this problem. Post-implementation results yielded a 54.87% reduction in material search and transportation times, a 32.86% reduction in travel times between stations, and a 19.81% increase in line efficiency. In addition, order fulfillment percentages increased from 12.5% to 60%.